Visual Evoked Potential in Migraine with Aura - Alshamrani, Foziah J.; AlSheikh, Mona Hmoud; Almuslim, Noora; Azman, Hatem Al; Alkhamis, Fahad; Nazish, Saima; Alnajashi, Hind; Alsulaiman, Abdulla (Medical Research and Its Applications Vol. 1, 2024)
Twelve percent of the world’s population suffers from migraines. A sizable portion of the world’s population suffers from migraines with aura. The purpose of this research is to describe the findings of a case-control study that was carried out to gain a better understanding of how migraine with aura manifests. The research looked at the P100 delay of the visual-evoked potential in both eyes of 92 healthy people and 44 patients who suffered from migraines with visual aura. All of the participants in the study were recruited from King Fahad University Hospital in Saudi Arabia. The information that was gathered was analyzed using SPSS Statistics version 21 and descriptive statistics were produced as a result. Both sets of people had the same ancestry and originated from the same location. Patients who suffered from migraines with aura exhibited a significantly shorter P100 delay in both eyes compared to healthy controls (p = 0.001), which is evidence that their early visual processing was distinct. In order to arrive at these findings, we compared people who suffer from migraines with aura to people who do not suffer from migraines and used them as subjects. This study might improve migraine treatment outcomes by understanding key biological processes and risk factors and creating personalized treatment plans that may help doctors to alleviate migraine symptoms and minimize their frequency and intensity. These findings also contribute to the ongoing attempts to bring the disease under control and provide vitally significant new information regarding the functioning of headaches with auras. The primary focus of study in the future should be on determining the nature of the connection between issues with early visual processing and headaches with aura.